Polysaccharides from the root of Angelica sinensis promotes hematopoiesis and thrombopoiesis through the PI3K/AKT pathway - Yang ST; Chen Jian L; Ye Jie; Cheng Sau; Lau Ching; Pong NH; Li Chi; Deng Ruixia; Liang Simon X; Meng Fan; Li Jianqin; Liu Chang; et al. (BMC, 2010)
Abstract Background Dozens of Traditional Chinese Medicine (TCM) formulas have been used for promotion of "blood production" for centuries, and we are interested in developing novel thrombopoietic medicines from these TCMs. Our previous studies have demonstrated the hematopoietic effects of DangGui BuXue Tong (DBT), a formula composed of Radix Angelicae Sinensis and Radix Astragali in animal and cellular models. As a step further to identify and characterize the active chemical components of DBT, we tested the hematopoietic and particularly, thrombopoietic effects of polysaccharide-enriched fractions from the root of Radix Angelicae Sinensis (APS) in this study. Methods A myelosuppression mouse model was treated with APS (10 mg/kg/day). Peripheral blood cells from APS, thrombopoietin and vehicle-treated samples were then counted at different time-points. Using the colony-forming unit (CFU) assays, we determined the effects of APS on the proliferation and differentiation of hematopoietic stem/progenitor cells and megakaryocytic lineages. Using a megakaryocytic cell line M-07e as model, we analyzed the cellular apoptosis progression with and without APS treatment by Annexin V, Mitochondrial Membrane Potential and Caspase 3 assays. Last, the anti-apoptotic effect of APS on cells treated with Ly294002, a Phosphatidylinositol 3-Kinse inhibitor (PI3K) was also tested. Results In animal models, APS significantly enhanced not only the recovery of platelets, other blood cells and their progenitor cells, but also the formation of Colony Forming Unit (CFU). In M-07e cells, we observed the anti-apoptotic effect of APS. Treatment by Ly294002 alone increased the percentage of cells undergoing apoptosis. However, addition of APS to Ly294002-treated cells significantly reduced the percentage of cells undergoing apoptosis. Conclusions APS promotes hematopoiesis and thrombopoiesis in the mouse model. This effect likely resulted from the anti-apoptosis activity of APS and is likely to involve the PI3K/AKT pathway.